A state-of-knowledge review on the endurance time method. (October 2020) - Estekanchi, Homayoon E.; Mashayekhi, Mohammadreza; Vafai, Hassan; Ahmadi, Goodarz; Mirfarhadi, Sayyed Ali; Harati, Mojtaba
Abstract: The endurance time method is a time history dynamic analysis in which structures are subjected to predesigned intensifying excitations. This method provides a tool for response prediction that correlates structural responses to the intensity of earthquakes with a considerably less computational demand as compared to conventional time history analysis. The endurance time method is being used in different areas of earthquake engineering, such as performance-based assessment and design, life-cycle cost-based design, value-based design, seismic safety, seismic assessment, and multi-component seismic analysis. Successful implementation of the endurance time method relies heavily on the quality of endurance time excitations. In this paper, a review of the endurance time method from conceptual development to its practical applications is provided. Different types of endurance time excitations are described. Features related to the existing endurance time excitations are also presented. Particular attention is given to various applications of the endurance time method in the field of earthquake engineering. Furthermore, challenges ahead for improving the existing ET motions or for developing future ET functions have been discussed briefly in the final section of the paper.